PENINGKATAN AKTIVITAS PESERTA DIDIK MENGGUNAKAN MODEL MERDEKA DI SDN TELUK TIRAM 5 BANJARMASIN - Rakasiwi, Sandrina Septia; Fathul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of student activity in learning, especially in IPAS content, is the focus of this study. This is because students tend to be passive and unenthusiastic during the learning process. To overcome this problem, the MERDEKA learning model was used, which is a combination of the Problem Based Learning, Student Team Achievement Division, and Make a Match models. This study aims to analyze the increase in student activity. The method used is Classroom Action Research (CAR), conducted over four sessions, with 10 fourth-grade students from SDN Teluk Tiram 5 Banjarmasin as subjects during the second semester of the 2024/2025 academic year. Qualitative data was obtained through observation, while quantitative data was obtained through written tests. Data analysis was conducted descriptively and presented in the form of tables and graphs. The results of the study showed a significant increase in the aspects studied. Student activity increased from 30% to 90% with the criterion “Almost Entirely Active.” The conclusion of this study is that the MERDEKA model is effective in increasing student activity and can serve as a reference in IPAS learning.